PENGARUH EDUKASI TERHADAP EFEKTIVITAS KONSUMSI TABLET FE DAN KADAR HB PADA IBU HAMIL - Ni Wayan Dian Ekayanthi; Gilang Purnamasari (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2020)
Anemia has negative impact on the growth and development of the fetus. Anemia potentially causing complications of pregnancy, childbirth, and even maternal and child mortality. Consumption of iron tablets has positive effect on increasing haemoglobin levels. The aim of this study was analyzed the effect of education on the effectiveness of iron tablets consumption and haemoglobin levels in pregnant women. Research design was quasi-experimental (non-equivalent-control group design). The subjects were 22 intervention groups and 22 control groups. Data analysis with Mc.Nemar, Mann Whitney, Wilcoxon and t test. There were significant differences in knowledge before and after the intervention in the intervention group, but in the control group instead, there was a significant difference in knowledge in the intervention group with the control group after the intervention, there was a significant difference in compliance with iron tablet consumption between the intervention group and the control group, there was significant differences in haemoglobin levels before and after intervention, both in the intervention and the control group, there were significant differences in the haemoglobin levels of pregnant women in the intervention group with controls. Conclusion: there is an effect of education on adherence iron tablets consumption and increased levels of haemoglobin in pregnant women.